Gender influence on the MVV / FEVı ratio in a population of healthy young adults - Soualiho Ouattara; Edwige Siransy‐Balayssac; Aya Liliane Kondo; Téniloh Augustin Yéo; Cyrille Serges Dah; Pascal Bogui (Physiological Reports, 2020)
Abstract Introduction Maximal voluntary ventilation (MVV) and flow expiratory volume in the first second (FEVı) are important spirometric parameters. They are both gender‐dependent. However, estimating the MVV, which is widely practiced in cardiopulmonary function testing, by multiplying FEVı by a constant value (equal to MVV/FEVı ratio) does not seem to take this into account. The purpose of this study was to compare the MVV/FEVı ratio by gender among healthy young adults. Methods This cross‐sectional prospective study involved 67 medical sciences students, including 36 females of the same race, height, and age group. Their ventilatory function was assessed using a computerized spirometer, according to international recommendations. Pearson's test made it possible to correlate different spirometric parameters and linear regression was established between MVV and FEVı. The nonparametric Kruskal–Wallis test was used to compare the MVV/FEVı ratio between females and males. Comparisons by gender were made also between our data and previous prediction equations. Results In both females and males, FEVı was the spirometric parameter with which MVV had the highest correlation (r = .91 in females, r = .63 in males). A comparison of the means of the MVV/FEVı ratio by gender showed a statistically significant (p < .005) decrease in females (35.68 vs. 38.87). The previous prediction equations showed statistically significant under and overestimation of MVV values when gender was not taken into account. Conclusion For the same height, age, and race, the ratio MVV/FEVı was significantly lower for females. So, the use of a preset constant value in estimating the MVV without taking gender into account was methodologically questionable. This work, which could have clinical implications, would benefit from being confirmed in a larger population.